Determinan Faktor Eksternal Terhadap Indeks Harga Saham Gabungan di Indonesia - Santoso, Alfin; Kurniawan, Mahrus Lutfi Adi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out how the dependent variable (IHSG) responds to fluctuations or shocks from the independent variables (Domestic Interest Rates, Foreign Interest Rates, World Oil, and the Dow Jones Index). The data used in this research is secondary data where this data was obtained from BI, The Fed, Nasdaq and Investing. The data used in this research is quarterly, namely IHSG data, Domestic Interest Rates, Foreign Interest Rates, World Oil and the Dow Jones Index for the period 2001-2022. The data analysis tool uses Vector Autoregression (VAR). The results of this research show that the JCI responded positively to shocks to the domestic interest rate variable and the Dow Jones index, while the foreign interest rate variable and world oil responded negatively.